2011
DOI: 10.3390/molecules16119739
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Oriented Design of Various Benzophenone Derivatives and Their in Vitro Antifungal and Antibacterial Activities

Abstract: A series of new substituted benzophenone derivatives was designed, synthesized and screened for their antifungal and antibacterial activities. The bioassays indicated that most of the synthesized compounds showed some antifungal activity against the tested phytopathogenic fungi, but lower antibacterial activities towards the five vibrios isolated from marine sources. The preliminary structure activity relationship (SAR) of the compounds was also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Finally, ortho -carboranyl hydrophilic ether compounds were generated from ( Z,Z ′)-1,1′-(4- ortho -Caboranyldimethyl)-bis(2-methoxyphenylethan-1-oxime) and side hydrophilic alkyl or aromatic halide reagents, followed by a treatment with potassium carbonate to result in the target compounds 4 – 8 (Scheme 2 ) [ 22 , 23 ]. A treatment of ortho -carborane (C 2 H 2 B 10 H 10 ) with aromatic halide as a base in tetrahydrofuran produced the target compounds 1 – 3 in moderate yields (1 93, 2 97, and 3 92%).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, ortho -carboranyl hydrophilic ether compounds were generated from ( Z,Z ′)-1,1′-(4- ortho -Caboranyldimethyl)-bis(2-methoxyphenylethan-1-oxime) and side hydrophilic alkyl or aromatic halide reagents, followed by a treatment with potassium carbonate to result in the target compounds 4 – 8 (Scheme 2 ) [ 22 , 23 ]. A treatment of ortho -carborane (C 2 H 2 B 10 H 10 ) with aromatic halide as a base in tetrahydrofuran produced the target compounds 1 – 3 in moderate yields (1 93, 2 97, and 3 92%).…”
Section: Resultsmentioning
confidence: 99%
“…26, No. 16 (2014), 5291-5294 research workers identified the antimicrobial potential of benzophenone nucleus and much research has been focused on the synthesis of its various derivatives for antibacterial and antifungal activities 20,21 .…”
Section: Synthesis and Antimicrobial Evaluation Of 2-aminobenzophenonmentioning
confidence: 99%
“…[21] Likewise, 1,2,3-triazole serves as an attractive heterocyclic group to connect two pharmacophores and biologically active fragments into one molecule to get progressive multifunctional compounds. [22][23][24][25][26][27] Moreover, the binding ability of 1,2,3-triazole framework with molecular targets due to their rigidity, high dipole moment, stability and capability to form hydrogen bonding under in vivo conditions has resulted in highly potent bioactive agents. [28,29] In view of the aforementioned biological significance, we decided to fuse coumarin, β-lactam, and 1,2,3-triazole pharmacophoric units into a single architecture using the concept of molecular hybridization.…”
Section: Introductionmentioning
confidence: 99%